Effect of anaerobic biodegradation with rumen liquor on nutrient composition of brewers’ dried grains (Indian Journal of Animal Production and Management, 2018)
Present experiment was conducted to assess the effect of anaerobic biodegradation on change in nutrient  composition of brewers’ dried grain (BDG). In 4 X 3 factorial experiment BDG was inoculated with rumen  liquor filtrate at the rate of 0, 10, 20 and 40% on volume/ weight basis. of BDG: inoculum for 3 different  durations of 2, 4 and 6 days to assess the change in nutrient compositios Which resulted in significant (p≤  0.05) increase in crude protein content from 24.72±0.35 to 34.30±0.35% and significant (p≤ 0.05) decrease  in crude fiber content from 26.03±0.36 to 14.41±0.36%.
Keywords: Biodegradation; Brewers’ dried grains; Nutrient composition; Rumen filtrate inoculum